Comparison of Avian Influenza Virus Contamination in the Environment Before and After Massive Poultry H5/H7 Vaccination in Zhejiang Province, China. (24th April 2019) - Cheng, Wei; Chong, Ka Chun; Lau, Steven Yuk-Fai; Wang, Xiaoxiao; Yu, Zhao; Liu, Shelan; Wang, Maggie; Pan, Jinren; Chen, Enfu
Abstract: Background: Information regarding comparison of the environmental prevalence of avian influenza virus (AIVs), before and after massive poultry vaccinations, is limited. Our study aimed to detect differences in the prevalence of AIVs type A and subtypes H5, H7, and H9 before and after the September 2017 massive poultry vaccination, across different sampling places and types. Methods: We collected 55 130 environmental samples from 11 cities in Zhejiang Province (China) between March 2013 and December 2018. Multivariate logistic regression analyses were conducted to determine the prevalence of AIV type A and subtypes H5, H7, and H9 across different sampling places and types, before and after massive poultry vaccination. Results: After the vaccination, contamination risk of AIV type A (adjusted odds ratio [aOR] = 1.08; 95% confidence interval [CI], 1.03–1.14) and subtype H9 (aOR = 1.58; 95% CI, 1.48–1.68) increased, and that of subtype H7 (aOR = 0.12; 95% CI, 0.10–0.14) decreased. Statistically significant decreased risk for H7 subtype contamination and increased risk for H9 subtype contamination were observed in backyard poultry flocks, live poultry markets, and slaughtering/processing plants. Swabs from poultry cages and slaughtering tables showed a statistically significant increased risk for H5 subtype contamination. The prevalence of H7 subtype decreased statistically significantly, whereas that of H9 subtype increased across the 5 sample types (poultry cages swabs, slaughtering table swabs, poultry feces, poultry drinking water, and poultry sewage). Conclusions: Despite the sharp decrease in H7 subtype prevalence, reduction measures for AIV circulation are still imperative, given the high type A prevalence and the increase in H9 subtype contamination across different sampling places and types. Abstract : Our study revealed differences in the prevalence of avian influenza virus type A and subtypes H5, H7, and H9, before and after massive poultry vaccination.